Optimal discretization for ill-posed integral equations with finitely smoothing operators - Solodky, S.G. (Український математичний вісник, 2008)
A new approach to the approximate solution of Fredholm integral equations of the first kind with finitely smoothing operators is worked out. It is established that on wide classes of such equations this approach allows to achieve the given level of accuracy at the minimal expense of the discrete information.